Melanopareia bitorquata (d’Orbigny & Lafresnaye, 1837) is a distinct species: an appraisal of morphological variation in the Collared Crescentchest Melanopareia torquata (zu Wied-Neuwied, 1831) (Aves: Melanopareiidae) - Lopes, Leonardo Esteves; Gonzaga, Luiz Pedreira (Zootaxa, 2016)
The Collared Crescentchest Melanopareia torquata is a poorly known and inconspicuous species of open savannas and grasslands in central Brazil, Paraguay and Bolivia. Three subspecies are currently recognized, but their taxonomic limits, ranges and conservation status are far from well-established. This paper analyses individual and geographic variation in this species on the basis of body measurements and plumage coloration of 119 specimens. A clinal pattern of body size variation and considerable mensural overlap precludes a clear-cut separation between the two subspecies restricted to Brazil, and there is evidently sexual dichromatism in some Brazilian populations. However, M. t. bitorquata shows highly distinct plumage features in parapatry with other forms, strongly suggesting it should be treated as a full species